(untitled) (Research, Society and Development, 2022)
Avoidable deaths are preventable deaths due to effective actions by health services that are accessible to the population. It is a sensitive indicator of the quality of health care. This study investigated 2,319 live birth deaths occurring in children under one year of age, born to mothers living in the city of Teresina, from 2008 to 2018. These variables were analyzed: Basic cause of death in the classification of preventable cause, ill-defined cause and cause not clearly avoidable. 72% of deaths were classified as preventable, 1% as ill-defined causes and 27% as not clearly preventable. The preventable infant mortality rate decreased from 17.79 deaths per 1000 LB in 2008 to 13.78 in 2018, showing a 27% reduction in cases. The subset of deaths reducible by adequate care for women during pregnancy in the early and late neonatal components predominated, and in the post-neonatal component the causes reducible by diagnostic actions and adequate treatment and reducible by health promotion actions linked to health care actions predominated. During the evaluated period, a reduction in the infant mortality rate was observed, however, there was also a high proportion of preventable deaths, suggesting a challenge to the organization of the three levels of health care.